Rabs, Rips, FIPs, and Endocytic Membrane Traffic - Rytis Prekeris (The Scientific World Journal)
Rab GTPases, proteins belonging to the Ras-like small GTP-binding protein superfamily, have emerged as master regulators of cellular membrane transport. Rab11 GTPase, a member of the Rab protein family, plays a role in regulating various cellular functions, including plasma membrane recycling, phagocytosis, and cytokinesis. Rab11 acts by forming mutually exclusive complexes with Rab11-family binding proteins, known as FIPs. Rab11-FIP complexes serve a role of targeting complexes by recruiting various membrane traffic factors to cellular membranes. Recent studies have identified several Rab11-FIP complex-binding proteins that regulate distinct membrane traffic pathways.